Death Across Cultures Death and Dying in Non-Western Cultures - Selin, Helaine; Rakoff, Robert M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Death Across Cultures: Death and Dying in Non-Western Cultures, explores death practices and beliefs, before and after death, around the non-Western world. It includes chapters on countries in Africa, Asia, South America, as well as indigenous people in Australia and North America. These chapters address changes in death rituals and beliefs, medicalization and the industry of death, and the different ways cultures mediate the impacts of modernity. Comparative studies with the west and among countries are included. This book brings together global research conducted by anthropologists, social scientists and scholars who work closely with individuals from the cultures they are writing about.
The Evolution of Funerary Ritual in Urbanizing China -- Belief in Karma and Mokṣa at the End of Life in India- Death and the Afterlife in Japan -- Return to Nature? Secularism and Politics of Death Space in Hong Kong -- Death and Dying: Belief, Fear and Ritual in Vietnamese Culture -- Negotiating Traditions and Modernity: Chinese Death Rituals in Singapore -- The Bureaucratic Professionalization of Funeral Rites in Tehran's Behesht-e Zahra Cemetery -- Death and Burial Practices in Contemporary Zulu Culture, South Africa -- Death in Botswana: Life Among the Ashes -- Ancestors and Death: From West Africa to Southwest Europe -- Living Coffins and Death Among the Ga of Ghana -- The Yoruba of Nigeria and the Ontology of Death and Burial -- Transformation of Funeral Rituals in Togo -- Rituals Around Life and Death in Mexico; The Day of the Dead -- Continuity and Ruptures in Brazilian Funeral Rites -- The Right to a Dignified Death in Argentina -- Superstar-Saints and Wandering Souls: The Cemetery as a Cultural Hotspot in Latin American Cities -- He taonga tuku iho: Indigenous End of Life and Death Care Customs of New Zealand Māori -- Communicating with the Dead in an Australian Aboriginal Culture: The Tiwi from Melville and Bathurst Islands -- Death and Dying in American Indian Cultures -- The Beauty of the Afterlife Among the Inuit of Nunavut -- Eternity Calling: Modernity and the Revival of Death and the Afterlife.
Keywords: Anthropology; Geriatrics; Social sciences; Humanities; Aging; Culture -- Study and teaching; Political sociology; Anthropology; Geriatrics; Humanities and Social Sciences; Ageing; Cultural Studies; Political Sociology